2021
DOI: 10.3390/agriculture11040358
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative Potential of Native Yeast Candida famata for Prokupac Grape Must Fermentation

Abstract: The fermentative potential of native Candida famata isolates from wild and cultivated blackberries was evaluated for potential application in Prokupac grape must fermentation. 5 isolates, out of a total 22 isolated yeasts, were identified as C. famata. After the initial screening of fermentative performances, microfermentation was performed in a sterile grape must. Produced samples were analyzed using the HPLC technique. All isolates showed an ability to grow at lower temperatures, good tolerance to 7% ethanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 51 publications
4
15
1
1
Order By: Relevance
“…The results correspond to the fact that M. pulcherrima is being used in the production of wines with low volatile acidity [18]. The used C. famata WB-1 strain has the potential for wine production with low volatile acidity [17]. Total content of polyphenols significantly depended on the used yeast strain and the application of sequential fermentation.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The results correspond to the fact that M. pulcherrima is being used in the production of wines with low volatile acidity [18]. The used C. famata WB-1 strain has the potential for wine production with low volatile acidity [17]. Total content of polyphenols significantly depended on the used yeast strain and the application of sequential fermentation.…”
Section: Discussionsupporting
confidence: 70%
“…Although pre-fermentative treatments should not affect the ethanol content, some researches indicated that 10 days of maceration induced a difference in ethanol content by more than 0.5% vol [33]. Reported ethanol content was higher than ethanol content of 11.3 and 12.6% produced by the same strain in red wine Prokupac [17], but these differences are most likely a consequence of the grape variety, initial sugar content and vinification procedure. A significant increase of 13-22% in the dry extract after cold maceration treatment of the must was observed compared to the wine samples produced without pre-fermentative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, with the exception of species C. zemplinina, C. californica , or C. famata [ 10 , 11 , 12 ], this group has been scarcely studied and reported. Candida yeasts associated with wine fermentations are characterized as being a good producer of glycerol and poor producer of acetic acid compared to traditional starter [ 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%